(untitled) (Islas, 2021)
Con la presente investigación se pretende mostrar los elementos distintivos del periodismo móvil y la factibilidad de adoptar estos en los medios de prensa cubanos. Luego de una amplia revisión bibliográfica, entrevistas y consultas a expertos se logró esbozar los pasos fundamentales para realizar cambios editoriales en los medios cubanos y las características que deben tener las nuevas redacciones. Se aportan elementos gráficos que ayudarían a la reestructuración de dichas redacciones. This research aims to show the distinctive elements of mobile journalism and the feasibility of adopting them in the Cuban press media. After an extensive literature review, interviews and meetings with experts, it was possible to outline the main steps to carry out editorial changes in the Cuban media and the characteristics that the new newsrooms should have. Graphic elements are provided that would help in the restructuring of these newsrooms.